Users’ experiences with the NoHow web-based toolkit with weight and activity tracking in weight loss maintenance: long-term randomized controlled trial - Mattila, Elina (2022)
©Elina Mattila, Susanne Hansen, Lise Bundgaard, Lauren Ramsey, Alice Dunning, Marlene N Silva, Marja Harjumaa, Miikka Ermes, Marta M Marques, Marcela Matos, Sofus C Larsen, Jorge Encantado, Inês Santos, Graham Horgan, Ruairi O'Driscoll, Jake Turicchi, Cristiana Duarte, António L Palmeira, R James Stubbs, Berit Lilienthal Heitmann, Liisa Lähteenmäki. Originally published in the Journal of Medical Internet Research (https://www.jmir.org), 10.01.2022. This is an open-access article distributed under the terms of the Creative Commons Attribution License (https://creativecommons.org/licenses/by/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work, first published in the Journal of Medical Internet Research, is properly cited. The complete bibliographic information, a link to the original publication on https://www.jmir.org/, as well as this copyright and license information must be included.